The Mediating Effect of Work Engagement on The Relationship Between Islamic Religiosity and Job Performance - Zahrah, Novia; Abdul Hamid, Siti Norasyikin; Abdul Rani, Shamsul Huda; Mustafa Kamil, Bidayatul Akmal (Universal Publishers, 2017)
The issues regarding job performance as well as work engagement have been widely discussed, yet surprisingly little research from an Islamic perspective conducted, especially Islamic religiosity and spirituality.Whereas, job performance and engagement of a Muslim should be examined based on Islamic perspective in order to sustain the productivity.Islam obligates all Muslim to perform the trust (amanah) given and work as a form of worship.While in dealing with difficulties, a Muslim is obligated to be patient, self-control, tawakal (trust) to Allah’s will, and believe that there is great wisdom behind everything that Allah does.These obligations can be fulfilled through the great awareness of Islamic religiosity.In fulfilling these obligations, the individual will put the best effort to engage and simultaneously perform well in their work.Therefore, in response to the impact of Islamic religiosity in enhancing work engagement towards sustaining job performance, this paper discussed this relationship empirically.Smart-PLS have been used as analytical tool.The data analysis results from a questionnaire survey on 150 Muslim employees indicates the significance of the proposed model.Future researchers are expected to study the issues in the workplace from Islamic perspective, such as Islamic job performance, Islamic work engagement, and so forth.